A case report of acute apendicitis in puerperium - Mojhová, M; Mikysková, I; Dubová, O; Homolková, E; Mašek, M; Zikán, M (Ceska gynekologie, 2019)
OBJECTIVE: This article stresses an impact of appropriate management work up in the diagnosis of acute apendicitis in puerperium. Atypical clinical symptoms may cause doubts in diagnosis and may delay necessary surgical intervention. DESIGN: Case report. SETTINGS: Department of Gynecology and Obstetrics, 1st Faculty of Medicine, Charles University, and Hospital Na Bulovce, Prague. METHODS: We present a case report describing an atypical presentation of acute apendicitis in early puerperium. Due to atypical course of the disease and atypical imaging locality and morphology, there were doubts about the diagnosis of acute apendicitis, patient was treated conservativelly and the disease later resulted in extensive surgical intervention. CONCLUSION: Acute appendicitis is the most common cause of non-urogenital morbidity in puerperium. Management of work up and timing of surgical intervention have key impact on maternal mortality and morbidity.
Keywords: Gynecology; postpartal; Pregnancy; Humans; sepsis; surgical intervention; poporodní období; Female; apendicitis; morbidita; lidé; non-urogenital morbidity; Appendicitis; ženské pohlaví; Morbidity; apendicitida; těhotenství; gynekologie; Acute Disease; Postpartum Period; akutní nemoc